Application of Marketing Mix in Home Industry: Focussed on Micro and Small-Scale Coffee Industries - Lya Aklimawati; Djoko Soemarno; Surip Mawardi (Indonesian Coffee and Cocoa Research Institute, 2016)
Differences in marketing strategies with other industries are needed to maintain business sustainability especially for facing fierce market competition. This research was aimed to identify a marketing mix implemented in micro and small scale coffee industries, and to identify external factors that affected business sustainability. This study was carried out in Sumberwringin Sub-district, Bondowoso District, East Java. Respondents of this study were 25 coffee industry players selected by using judgement sampling method. Primary and secondary data were collected in this study. Data were analyzed with descriptive-qualitative method and interactive analysis. The results showed that micro and small-scale coffee industries was still implementing conventional marketing pattern. The marketing mix which applied in coffee industry, were (a) the product mix was not persistent that depended on consumer demand; (b) selling price of product was determined from cost production and profit margins; (c) distribution was conducted with active and passive marketing particularly based on customer orders; (d) promotion mix was implemented by direct marketing, personal selling, and word of mouth. Micro-environments of the marketing affecting micro and small-scale coffee industries were: (a) customers as main target market in form of consumer markets and alternative target market as re-seller markets; (b) high intensity competition as a result of large number of competitors and lack of product diversification; (c) many raw material suppliers, but expensive input production cost; (d) there was no a marketing partnership with marketer agent/other partner, but it had strategic partnership with supplier and government; (e) government policies on product development and marketing had been implemented by facilitating exhibition activity, processing equipment, and training.